Key Topics and Case Studies in Pragmatics: Examples of Corpus-based Research - Mohammad Amin Hawamdeh; Mohammad H. Al Aqqad; Ahmad Ali Mahamdeh (WISE Pendidikan Indonesia, 2025)
This study examines the reliability and applicability of corpus-based methods for investigating pragmatic phenomena, with a focus on the Arabic–English language pair. Three case studies are presented: (1) the conventionality of language in Quranic translations, (2) conversational implicature in sacred text dialogue, and (3) hedging strategies in political discourse. Adopting a qualitative case study design supported by corpus-driven analysis, the research integrates thematic interpretation with quantitative frequency data to uncover context-sensitive patterns in meaning construction. The findings demonstrate that operationalizing stylistic conventions in sacred texts enables replicable annotation frameworks for both translation studies and digital religious discourse; that implicature analysis can reveal culturally nuanced meaning negotiation relevant to online communication; and that hierarchical mapping of hedging functions provides a transferable model for monitoring rhetorical strategies in both traditional and digital political messaging. This integration advances corpus pragmatics beyond descriptive analysis toward predictive and comparative modeling, offering methodological and theoretical contributions applicable across multilingual, cross-cultural, and technology-mediated contexts. The study underscores the value of corpus-based pragmatics as a unifying framework for understanding language use in hybrid communicative environments, from religious translation platforms to social media political discourse.